Penetration performance of protective materials from crossbow attack: a preliminary study - Read, James; Hazael, Rachael; Critchley, Richard (Springer, 2024)
Crossbow-related injuries resulting in serious and mortal consequences have increased in recent years, and although significant research exists for both injury and fatality on the human body, limited data exists on the lethality of the bolt and the failure modes of protective materials. This paper concerns itself with the experimental validation of four differing crossbow bolt geometries, their effects on material failure and potentially lethality. During this study, four different types of crossbow bolt geometries were tested against two protection mechanisms that differed in mechanical properties, geometry, mass and size. The results show that at 67 ms−1, ogive, field and combo tips do not provide lethal effect at 10-m range, whilst a broadhead tip will perforate both the para-aramid and a reinforced area of polycarbonate material consisting of two 3-mm plates at 63–66 ms−1. Although perforation was apparent with a more honed tip geometry, the chain mail layering within the para-aramid protection and friction caused by polycarbonate petalling on the arrow body reduced the velocity enough to demonstrate the materials under test are effective at withstanding crossbow attack. Subsequent calculation of the maximum velocity that arrows could achieve if fired from the crossbow within this study shows results close to the overmatch value of each material and therefore a requirement to advance the knowledge in this field to influence the development of more effective armour protection mechanisms.
Keywords: Kinetic energy density; Impact; Polycarbonate; Para-aramid; Ballistic gel; Bolts